SGLT-2 inhibitors: new effective drugs for treatment of heart failure - Olgierd Król; Konrad Gładysz; Justyna Szydłowska; Olga Żuchnik; Piotr Kwiatkowski; Magdalena Czelej; Aleksander Kłos; Krzysztof Gieroba; Marcin Szydłowski; Paweł Zuchniak (Kazimierz Wielki University, 2022)
Introduction: SGLT-2 inhibitors having selectivity to sodium glucose cotransporter 2 were introduced on the market in 2012 as drugs for the pharmacotherapy of type 2 diabetes. Aim of the work: To summarize the current state of knowledge about the drugs: SGLT-2 inhibitors and their mechanism of action and application in cardiology. Materials and Methods: A review of the literature available in PubMed and Google Scholar database was conducted. Results: In addition to glucosuria, the diuretic effect is caused by natriuresis. A study was conducted, after which it was deduced that the natriuretic effect of empagliflozin did not depend on the degree of renal dysfunction, and was exacerbated under the influence of loop diuretics. SGLT-2 inhibitors reduce cardiac preload. Flozins also lead to a reduction in afterload. The DAPA-HF study of 4744 patients with HF, taking 10 mg of dapagliflozin or placebo. The primary outcome of the study, was data in the form of death from cardiovascular causes or exacerbation of heart failure. These accounted for 16.3% in the flozin group compared to 21.2% in the control group. Adverse events were rare. Dapagliflozin was effective in 55% of subjects, in both patients and non-diabetics with type 2 diabetes. EMPEROR-REDUCED studied the effect of taking 10 mg of emagliflozin or placebo in 3730 patients. Flozin reduced the risk of cardiovascular death and hospitalizations. Fewer deaths from any cause were also observed. Summary: Both studies highlighted significant benefits of SGLT-2 inhibitors- they reduced the risk of death from any cause and from cardiovascular causes. The therapeutic benefits, regardless of the degree of renal dysfunction, the synergy with other drugs in heart failure, and the low number of serious side effects, led to the inclusion of flozins in the latest ESC 2021 guidelines for therapy in heart failure with reduced ejection fraction, regardless of the presence of diabetes.